Inter-company profitability analysis of Indian general insurance industry - Sur, Debasish (1999)
A comparative profitability analysis of Indian insurance companies using 4 major profitability indicators (return on operating assets, return on capital employed - net & gross and return on net worth). - Reproduced
Keywords: Insurance - India; Insurance